What spurs up Employee Engagement: An Empirical study in Uttar Pradesh, India - Dr. Kushendra Mishra, Mohit Kumar, (International Journal of Scientific Research and Management (IJSRM), 2014)
The world has become a smaller place to play where competition has become the name of the game. All eyes are on the most crucial and essential resource of any organization i.e. human resource. There are only two most difficult things in an organization. One is to recruit and select employees and second is to sustain them in the company over a period of time. The latter being arguably the illusory thing witnessed with utmost rarity. With a blitzkrieg pace of the business, each organization tries to capitalize on any potential weakness of the opponent market player and perhaps the growing dissent and dissatisfaction among employees could make or break for any organization climbing up the ladder. Employees hence play a pivotal role in the dynamics of the organization and hence need to cultivate what is called a sense of organizational citizenship. Employee engagement - an extension of the latter concept is still an emerging area which has been a talking point over a last decade. This refers to the situation when employees consider themselves as part and parcel of the organization whereby mutual growth of employees is harnessed to leverage the success rate of the organization.Such an endeavor is possible only when employee engagement initiatives are given shape and direction. However, initiatives could only be prudent if the underlying parameters of the construct could be well analyzed. This research paper tries to gauge all determinants and variables which ultimately consolidate into a final construct of employee engagement. The study is specific to primary schools in Uttar Pradesh where an attempt is made to chalk out all possible influences responsible for a conspicuous lower level of employee engagement.